ҚАРАҚАЛПАҚ ТИЛИНДЕ ҮСТКИ КИЙИМДИ БИЛДИРЕТУҒЫН АТАМАЛАРДЫҢ ЛИНГВИСТИКАЛЫҚ АНАЛИЗИ - Зайрова, Қ. (НАУКА и ОБЩЕСТВО, 2021)
This article provides a linguistic analysis of the names of outerwear items as one of the types of material culture of the Karakalpak people that have survived several historical eras and have come down to our days. The article talks about warm outerwear such as tun, pustin, ichuk, chakmon, chapan, coat, fur coat, raincoat, etc. The lexical meaning of the long forgotten names of outerwear, are revealed their borrowing, use and place in the lexical layer of the language.
Keywords: историческая лексика; лингвистический анализ; термин; заимствованные слова; лексика предметов одежды; ичук; чакмон; чапан; пальто; шуба; плащ